Potassium Iodide in Dermatology- Recent Advances in Mechanism of Action, Preparation, Uses and Adverse Effects - Nishant Goel; Bhavana R. Doshi (Indian Journal of Dermatology)
Potassium iodide (KI) is a simple yet versatile drug. It has been successfully used for the treatment of various diseases in dermatology, but there are very limited studies on the exact mechanism of action, preparation, and dosage of potassium iodide, causing concerns regarding its toxicity. This article reviews the multimodal mechanism of action of KI and standardises the method of preparation of a saturated solution of potassium iodide (SSKI) on an OPD basis. It also lists the existing and newer indications, optimal dosages, adverse effects, and contraindications of potassium iodide, thereby enabling the proper utilisation of this age-old remedy as a cost-effective yet safe treatment option for various inflammatory dermatoses, including panniculitis (erythema nodosum, erythema induratum, subacute nodular migratory panniculitis), Wegener’s granulomatosis, granuloma annulare, Behcet’s syndrome, pyoderma gangrenosum, Sweet’s syndrome, and erythema multiforme. Potassium iodide is also used for fungal infections, including cutaneous and lymphocutaneous sporotrichosis, cutaneous cryptococcosis, entomophthoramycosis, human pythiosis, chromoblastomycosis, and mucormycosis.